2010
DOI: 10.1002/jmv.21845
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of lamivudine resistance mutations in Brazilian patients co‐infected with HIV and hepatitis B

Abstract: This study analyzed the genotype distribution and frequency of lamivudine (LAM) and tenofovir (TDF) resistance mutations in a group of patients co-infected with HIV and hepatitis B virus (HBV). A cross-sectional study of 847 patients with HIV was conducted. Patients provided blood samples for HBsAg detection. The load of HBV was determined using an "in-house" real-time polymerase chain reaction. HBV genotypes/subgenotypes, antiviral resistance, basal core promoter (BCP), and precore mutations were detected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 36 publications
3
16
0
Order By: Relevance
“…The prevalence in 3TC monotreatment is about 40–77.8% among those who receive 3TC treatment for 1 year or longer [22, 23]. 3TC resistance may occur in a small proportion of patients during 3TC plus TDF treatment [24, 25]. In this study, a very high prevalence (76.4%) of 3TC resistance was found in patients on HAART, including 3TC plus TDF.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The prevalence in 3TC monotreatment is about 40–77.8% among those who receive 3TC treatment for 1 year or longer [22, 23]. 3TC resistance may occur in a small proportion of patients during 3TC plus TDF treatment [24, 25]. In this study, a very high prevalence (76.4%) of 3TC resistance was found in patients on HAART, including 3TC plus TDF.…”
Section: Discussionmentioning
confidence: 70%
“…However, certain co-infected patients exhibit incomplete viral suppression, with persistent, and sometimes transient bouts of HBV replication [27, 28]. Up to 17% of patients developed virological breakthrough during 3TC plus TDF treatment [24, 25, 29]. In this study, 8.8% of patients on HAART developed virological breakthrough.…”
Section: Discussionmentioning
confidence: 72%
“…We do not know whether the HBV strains that showed decreased antigenicity could escape the neutralizing action of the anti-HBs antibodies induced by vaccination and cause infection in previously vaccinated individuals (Torresi et al 2002, Matthews et al 2006. Various studies in HBV-HIV co-infected patient populations have evaluated the presence and clinical importance of these mutations (Matthews et al 2006), but in Brazil few studies have evaluated this matter (Santos et al 2004, Sucupira et al 2006, Mendes-Correa et al 2008. If these mutations are indeed associated with vaccine escape, they would have an important impact on public health.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, the presence of genotype G has been rarely seen (Lobato et al 2006, Mendes-Correa et al 2008. Bottecchia et al (2008) identified genotype G in a patient infected with HBV only and in two patients co-infected with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Genotype D is the most frequent in Southern Brazil, whereas genotype A is the most frequent in all other regions [67,68]. In Italy, genotype D is largely the most frequent and is found in 73 to 80% of the patients infected with HBV [69,70] Genotype F is the most divergent and considered indigenous in the Americas.…”
Section: Resultsmentioning
confidence: 99%